Gastric cancer radiation therapy: a bibliometric analysis of the scientific literature - Weng, Zhen-Hong; Chen, Bin-Bin; Lin, Jia-Rui; Xu, Mu-Ming; Yuan, Jin-Peng; Hu, Hao-Kai (Frontiers in Oncology, 2025)
Background and objectivesGastric cancer is a common malignant tumor primarily treated through surgery. Concurrently, radiation therapy has gained attention as an important local treatment modality. However, its application in gastric cancer remains limited, with ongoing debates on radiation standards. Given that bibliometrics serves as a potent tool to unveil scientific literature, we conducted a bibliometric analysis of literature on radiation therapy for gastric cancer. We explored emerging trends, common patterns in research, tracked collaborations and networks, and anticipated future directions in this clinical context.Materials and methodsWe searched the electronic Web of Science (WOS) database using keywords “gastric cancer” and “radiation therapy” for manuscripts published in English from 2014 to 2023. Data analysis was conducted using R-Studio software, employing bibliometric methods based on the bib liometrix R package. Quantification involved assessing the most relevant authors based on document production and citation metrics. Author productivity was analyzed using Lotka’s law. Main thematic areas included isolated (niche) topics, emerging topics, hot (motor) topics, and necessary (basic) topics.ResultsA total of 2405 documents were initially retrieved, from which 484 articles closely related to gastric cancer radiation therapy were selected, showing an annual growth rate of -2.05%. Overall, publications were found in 186 different journals, with “FRONTIERS IN ONCOLOGY” being the most relevant journal. The most prolific authors were from South Korea. Clinical trials (survival, phase III clinical trials) and treatment strategies (surgery, chemotherapy, radiation therapy, perioperative treatment) represented the fundamental topics. Emerging topics included radiation dose, therapeutic response and immunotherapy.ConclusionRadiation therapy for gastric cancer has evolved in terms of timing, modes, target sites, and emerging combination therapies. It benefits patients with potentially resectable, unresectable, or isolated distant metastases. Immunotherapy combined with radiation shows significant potential and could become a new breakthrough in treatment strategies.